Utilization of Audio Visual Media in The Subject of Islamic Cultural History at MI Miftahul Falah Karangrejo Tulungagung - Madani, Ittikhadul; Khabib, Khamdan Choirul; Purwowidodo, Agus; Huda, Muh. Nurul (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
This research is motivated by a phenomenon that still occurs in the development of elementary school students' education, namely difficulties in the study of Islamic Cultural History. The difficulty of Islamic Cultural History lessons in students is caused by an inappropriate learning process that results in students not having the interest and desire to learn the lesson well. This research was conducted at Miftahul Falah Islamic Elementary School using a qualitative research approach, as for the type using descriptive qualitative research. Data were collected through interview, observation and documentation methods. In analyzing the data using data reduction, presenting data and drawing conclusions. Meanwhile, to check the validity of findings using data triangulation, the triangulation used is source triangulation and method triangulation. The results of this study are as follows: (1)  How use audio-visual media in the subjects of Islamic Cultural History Miftahul Falah Islamic Elementary School Karangrejo, namely preparing learning and learning tools, starting learning activities with greetings, smiles and greetings, displaying Ice Breaking as the beginning of a fun lesson, showing short films, conducting learning evaluations using power points by displaying tests / questions Short duration and directly answered by students in each assignment book individually without rewriting the questions. (2)  The results of the use of audio-visual media in the subject of Islamic Cultural History at Miftahul Falah Islamic Elementary School Karangrejo, namely audio-visual media are used for learning media, ice breaking, as well as learning resources, making it easier for students to master the material, changing students' mindsets from bored to happy with Islamic Cultural History subjects, increasing student achievement, helping teachers in terms of energy and time efficiency,  motivating students to continue learning Islamic Cultural History, realizing learning goals effectively and efficiently. (3) Obstacles to the use of audio-visual media in increasing students' understanding of the subject of Islamic Cultural History at Miftahul Falah Islamic Elementary School Karangrejo are sometimes electricity failures, when the power failure requires a jenset. But in this case the school still does not have a private jenset facility. In addition, the number of crowded children resulted in a less conducive classroom atmosphere.